Development of Functional Transition Metal Oxide and Sulfide Cathodes for Aqueous Zinc-Based Rechargeable Batteries - Zhong, Yijun (Curtin University, 2020)
Transition metal oxides and sulfides are promising multi-functional cathode materials for zinc-based batteries. Herein, new cathode materials are developed based on rational designs for promoting kinetics of redox reactions and facilitating the electronic and mass transfer, demonstrating improved performance and stability of the batteries. Multiple material characterizations combined with electrochemical analysis are utilized to investigate the material properties and provide a better understanding of mechanisms behind the improved results.